Relationship of cigarette consumption with academic performance in university students - Choque Vera, Ronald (2017)
In the present research it is analyzed the relationship between the consumption of cigarettes and the academic achievement in a group of students from a private university in Arequipa. In order to collect the data, it was selected a random sample composed by 464 students of nine professional careers; 40,52 % of them were male and 59,48 %, female. It was taken the Fargerstrom Test for Smoking, finding that only 1 % of the sample could be considered as cigar dependent; meanwhile, in predictive data processing, through regression analyses, we found that the students with higher punctuation in Fargerstrom Test have low academic achievement, and the semester of studies predict positively the academic achievement.